Analisis Tingkat Pengetahuan Pasien tentang Penggunaan Obat Kortikosteroid di Apotek Banyubiru Sehat - Sholeh, Aries Badrus; Fatmasari, Heni; Tri Handayani, Setya (Indonesian Journal of Medical and Pharmaceutical Science, 2025)
Background: Corticosteroids are widely used medications with potent anti-inflammatory and immunosuppressive effects. However, improper use without sufficient patient understanding can result in serious adverse effects, such as hypertension, osteoporosis, hyperglycemia, and Cushing’s syndrome. Preliminary observations at Banyubiru Sehat Pharmacy revealed high levels of corticosteroid purchases without prescriptions or proper patient knowledge. This highlights the importance of assessing patients’ understanding to ensure rational use. Methods: This descriptive observational study was conducted at Banyubiru Sehat Pharmacy in May 2025. Data were collected from 75 patients who had previously used corticosteroids, selected through purposive sampling. A validated and reliable questionnaire was used to evaluate their knowledge. Responses were analyzed using descriptive statistics and categorized into three levels: good (>75%), moderate (60–75%), and poor (<60%). Results: The majority of patients (66.67%) demonstrated a poor level of knowledge regarding corticosteroid use. Only 13.33% showed good understanding, while 20% had moderate knowledge. The average correct response rate was 46.4%. Most patients lacked awareness of the long-term risks and proper indications of corticosteroid therapy. Conclusion: Patients' knowledge of corticosteroid use at Banyubiru Sehat Pharmacy was predominantly low. Educational interventions, including counseling and informative materials, are needed to enhance patient awareness and promote safe, rational drug use.